Ombudsman: evaluating the access to health services - Luciana Rocha de Oliveira Nardo; Carmen Maria Casquel Monti Juliani (Universidade Federal do Ceará, 2012)
This study aimed at identifying and analyzing quantitative data of the complaints of the public Ombudsmen Sector in the city of Marilia-SP. This is a documentary and epidemiological study, inserted in the field of evaluation of health services. We analyzed 529 complaints to the ombudsman arising from the core network. The results showed that the largest number of complaints is related to the pent-up demand for medical specializations, followed by the poor service of Primary Care, the lack of medicine and the pent-up demand examinations. We deepened the analysis of complaints regarding the difficulty of access to medical specializations being: 62.0% originated from Basic Health Units, 66.4% of users were allowed access after the claim; 69.0% received feedback and 45.4% of the registers were not in the evaluation of the Coordination of Primary Care. It is known that the ombudsman is a powerful tool for assessing health services.